Flow, Centering, and the Classroom: Wisdom from an Ancient Friend - Lorie Heggie (Journal of the Assembly for Expanded Perspectives on Learning, 2001)
Understanding "flow" and drawing on the metaphor of the dialectic that occurs between horse and rider can guide us to create a centered classroom.